Mobile Phone-Based Health Reminders on Treatment of Tuberculosis Patient Relapse - Djuma, Elviera; Hariyati, Rr. Tutik Sri; ., Masfuri (POLITEKNIK KESEHATAN KEMENTERIAN KESEHATAN MANADO, 2023)
Abstract Background: Treatment nonadherence is multifaceted, complex, and a significant barrier to TB control and contributes to the spread of disease and death. Mobile phone-based strategies have been used in programs to increase the adherence of tuberculosis patients to taking medication. Objective: To determine the effectiveness of using cell phone-based health reminders on the adherence of tuberculosis patients to treating their disease. Methods: An online database of academic journals is used with a literature review method using the keywords